2005
DOI: 10.1089/ars.2005.7.32
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Induces Glutathione Biosynthesis and Inhibits NF-κB Activation and Interleukin-8 Release in Alveolar Epithelial Cells: Mechanism of Free Radical Scavenging Activity

Abstract: Oxidants and tumor necrosis factor-alpha (TNF-alpha) activate transcription factors such as nuclear factor-kappaB (NF-kappaB), which is involved in the transcription of proinflammatory mediators, including interleukin-8 (IL-8). Curcumin (diferuloylmethane) is a naturally occurring flavonoid present in the spice turmeric, which has a long traditional use as a chemotherapeutic agent for many diseases. We hypothesize that curcumin may possess both antioxidant and antiinflammatory properties by increasing the glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
234
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(254 citation statements)
references
References 28 publications
13
234
0
7
Order By: Relevance
“…Curcumin has been shown to induce GSH biosynthesis [5]. It is unlikely that curcumin reacts with GSH directly under our conditions, as Oetari et al, 1996 showed that GSH prevents the instability of curcumin in phosphate buffer at pH 7.4 [53].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Curcumin has been shown to induce GSH biosynthesis [5]. It is unlikely that curcumin reacts with GSH directly under our conditions, as Oetari et al, 1996 showed that GSH prevents the instability of curcumin in phosphate buffer at pH 7.4 [53].…”
Section: Discussionmentioning
confidence: 79%
“…Extensive research within the last half-a-decade has confirmed that curcumin mediates anti-inflammatory effects through the downregulation of transcription factor nuclear factor-κB (NF-κB) [1,2] tumor necrosis factor (TNF) [3], interleukin-6 (IL-6) [4], interleukin-8 (IL-8) [5], adhesion molecules [6], inducible nitric oxide synthase (iNOS) [7], matrix metalloproteinase-9 (MMP-9) [8], cyclooxygenase-2 (COX-2) [9], and 5-lipoxygenase (5-LOX) [10]. In fact, curcumin has been shown to bind to an active site in 5-LOX, and the two together have been cocrystallized [11].…”
Section: Introductionmentioning
confidence: 99%
“…These results show that acrylamide causes a signifi cant decrease in antioxidant parameters. Acrylamide especially decreases the GSH and GST activity levels of cells, spoils the oxidant/antioxidant balance against the oxidants and thus leads to oxidative damage in cells (1,14,(50)(51)(52)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Biswas et al [34] found that curcumin has antiinflammatory and antioxidant properties with a potent ability to inhibit reactive oxygen species formation. Azab et al [5] reported that in gentamicin treated Guinea pigs, there were physiological and structural changes in the kidney.…”
Section: Curcumin (Curcuma Longa L)mentioning
confidence: 99%